SAT0293 Association between Clinical Presentation and Blindness in Gca, and Effects of Gca-Related Visual Loss on Morbidity, Mortality and Quality of Life. (10th June 2014) - Elsideeg, S.; Borg, F.A.; Williams, M.; Patil, P.; Dasgupta, B.
Abstract : Background: Acute visual loss is a catastrophic irreversible complication of Giant Cell Arteritis (GCA). We describe the relationship of GCA related blindness with various patient related factors at presentation. We also report morbidity, mortality and effect on quality of life after sight loss. Objectives: To explore the association between sight loss and presenting clinical, laboratory, histology and ultrasound features, and to describe the impact of sight loss from GCA on morbidity, mortality and quality of life. Methods: From 2009-2013, 115 patients were diagnosed with GCA by ACR criteria at our centre. 19 (16.5%) of these presented with unilateral or bilateral sight loss. We performed retrospective review of the hospital records of these 19 patients, and of our GCA Fast Track Pathway clinic database. We recorded demographic, clinical, laboratory, biopsy and ultrasound finding, and symptom to steroid time. We also reviewed the case notes for subsequent inpatient admissions, causes of death and discharge destination. EQ5D scores at baseline and 6 months were taken from our Fast Track Pathway database. Results: Of 19 patients with sight loss, 14(73.7%) were female, mean age 86. Most patients presented with herald ischaemic features before onset of blindness; 17/19 (85%) described jaw claudication or blurred vision. The second commonest clinical presentation (in 15 (79%) patients) was classical headache, scalp tenderness and thickened temporal artery. 68.5% described constitutional upset, particularly night sweats, weight loss and fatigue. Polymyalgic symptoms were only seen in 4 (21%) patients with visual loss, and fever in just one (5.2%). The mean delay from symptom onset to starting steroid in patients with visual loss was 27.1 days (range 3-84). 18 patients (94.7%) were temporal artery biopsy positive. The clinical and laboratory picture of the remaining patient was classical for GCA. All 19 cases underwent temporal artery ultrasound. 14 (73.7%) were found to be halo sign positive. Morbidity, Mortality and Quality of Life (QOL): All 19 patients with visual loss required inpatient admission more than once following sight loss, with pneumonia and urinary tract infection the commonest causes of admission. 3 (15%) suffered femoral fracture, and 3 (15%) poorly controlled diabetes or ketoacidosis. Overall, there were 64 inpatient episodes (mean number/patient 3.4). Mean length of hospital stay was 23.9 days, with total 453 bed days in this patient group. QOL, assessed by EQ5D at baseline and 6 months, was adversely affected in this patient group. All 19 experienced some degree of depression related to loss of independence, impaired mobility and loss of confidence. Mean Health Score was 61.2/100 (range 45-80), reflecting significantly worse quality of life after sight loss. 7 (36.8%)required residential home admission due to their blindness. 5 (26.3%)patients died, 4 in the first year post diagnosis, 1 in the second year. Cause of death was: myocardial infarction (2 cases), pneumonia (1 case), pulmonary embolus post femoral fracture (1 case). Conclusions: Herald cranial ischaemic symptoms and delayed steroid commencement in GCA are associated with high incidence of permanent sight loss. Blindness due to GCA is associated with significant mortality, morbidity, reduction in quality of life and loss of independence. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5303